2005
DOI: 10.1182/blood-2004-05-1846
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of SU11248 in the treatment of patients with refractory or resistant acute myeloid leukemia (AML) or not amenable to conventional therapy for the disease

Abstract: Fifteen patients with refractory AML were treated in a phase 1 study with SU11248, an oral kinase inhibitor of fms-like tyrosine kinase 3 (Flt3), Kit, vascular endothelial growth factor (VEGF), and plateletderived growth factor (PDGF) receptors. Separate cohorts of patients received SU11248 for 4-week cycles followed by either a 2-or a 1-week rest period. At the starting dose level of 50 mg (n ‫؍‬ 13), no dose-limiting toxicities were observed. The most frequent grade 2 toxicities were edema, fatigue, and oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
276
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(283 citation statements)
references
References 30 publications
4
276
0
3
Order By: Relevance
“…Several trials combining TKI and conventional chemotherapy are ongoing in patients with newly diagnosed FLT3-mutant AML or in AML in relapse. [221][222][223][224][225][226][227][228][229] TKI may also target c-KIT mutations, although in such cases the exact location and nature of the mutation must be determined individually because specific inhibitors are active against particular c-KIT mutations. For example, cells carrying insertion/deletion in exon 8, ITD of exon 11 and 12 or substitutions at codon 822 are sensitive to imatinib, while D816 mutations confer a resistance to imatinib but can be targeted with other TKI such as midostaurin, nilotinib or dasatinib.…”
Section: Gene Mutations As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Several trials combining TKI and conventional chemotherapy are ongoing in patients with newly diagnosed FLT3-mutant AML or in AML in relapse. [221][222][223][224][225][226][227][228][229] TKI may also target c-KIT mutations, although in such cases the exact location and nature of the mutation must be determined individually because specific inhibitors are active against particular c-KIT mutations. For example, cells carrying insertion/deletion in exon 8, ITD of exon 11 and 12 or substitutions at codon 822 are sensitive to imatinib, while D816 mutations confer a resistance to imatinib but can be targeted with other TKI such as midostaurin, nilotinib or dasatinib.…”
Section: Gene Mutations As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Expression of Mcl-1 is upregulated at the transcriptional level by STAT5, PI3K/Akt and Mek/Erk pathways [11][12][13] and at the posttranslational level by the PI3K/ Akt pathway. 14 It has been reported that FLT3 inhibition induces apoptosis in leukemic blasts of AML patients who carry the FLT3 mutation, [15][16][17][18][19][20][21] though the mechanism remains unknown. Several FLT3 inhibitors have been developed, including sorafenib (BAY43-9006), lestaurtinib (CEP-701), PKC412, sunitinib (SU11248) and tandutinib (MLN-518), but clinical trials using these inhibitors as single agents have not been successful.…”
Section: Introductionmentioning
confidence: 99%
“…Several FLT3 inhibitors have been developed, including sorafenib (BAY43-9006), lestaurtinib (CEP-701), PKC412, sunitinib (SU11248) and tandutinib (MLN-518), but clinical trials using these inhibitors as single agents have not been successful. [17][18][19][20][21] Conventional chemotherapy in combination with FLT3 inhibitors has therefore emerged as the preferred therapeutic strategy in the current phase 3 trials. [17][18][19] It is conceivable that targeting multiple arms of the apoptotic regulatory machinery with FLT3 inhibition would be more efficacious than targeting the mutated FLT3 alone.…”
Section: Introductionmentioning
confidence: 99%
“…In a Phase I trial, KW-2449 treatment led to transient decreases in peripheral blast counts (Cortes et al, 2008;Pratz and Levis, 2008;Pratz et al, 2009 (Fiedler et al, 2005;Kancha et al, 2007;O'Farrell et al, 2003a, b), as well as the piperazinyl quinazoline MLN518 (tandutinib; CT53518; Millennium, Cambridge, MA, USA) (Kelly et al, 2002b;Cheng and Paz, 2008). There is presently an ongoing Phase I/II trial investigating SU11248 combined with standard chemotherapy in mutant FLT3-positive AML patients over the age of 60 years.…”
Section: Kinase Inhibitors Under Clinical Investigation For Mutant Flmentioning
confidence: 99%